Green energy generation by turbine rotation due to magnetic forces - Terence Anak Slyvester Empari (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Back to past decades, green energy has been introduced regarding the global warming issues related to usage of the non-renewable energy. However, the available renewable energy has limitation and mostly related to location to operate the renewable energy. Hence, magnet forces turbine is introduced. This concept allowed the forces of the magnet to induce kinetic motion to the discs thus the kinetic energy will be converted into eletricity energy. Unfortunately, the idea is known as perpetual motion.